Integration of ethics in Malaysian corporate governance practices / Zaleha Othman - Othman, Zaleha (2011)
Corporate governance systems are developed to manage business affairs with the aim of enhancing shareholder wealth and corporate accountability. However, despite the many efforts made, corporate governance flaws ( i.e corporate scandals) keep emerging, making this phenomenon a major governance issue. Various opinions have been articulated in response to this and ethics have been strongly recommended as a factor to solve the corporate governance issue. Motivated by the above, this research examines the possibility of integrating ethics into corporate governance practices. The research develops conceptual foundation around the dimension of social contract theory. Associated with the subjective nature of the research, the research employed social constructionist ontology, and the process involved a qualitative approach (i.e enquiry). Interpretive analysis techniques are employed to support the qualitative approach. The qualitative approach provides rich description in exploring the subjects' minds i.e. prominent corporate governance experts, and corporations which are known for their good corporate governance reputation. Based on the interpretive analysis conducted, the research findings answered the research questions. Social constructed views of respondents indicate understanding of corporate governance as a social process requiring pluralistic governance in which, support from the social dimension i.e ethics, is crucial. Support from ethics includes practice of several key ethics contents (such as organizational ethics structure, ethical management, ethical leadership and ethical culture). Emergence of the key ethics contents articulates the process of ethics integration into corporate governance practices. However, the respondents perceived that integration of ethics is still in its infancy. This is due to the influence of combinations of forces. Positive forces such as financial pressure, business pressure and external pressure influence integration of ethics. Negative forces such as internal governance matters, power, political influence, economic desire and lack of knowledge deter the corporations from considering integrating ethics into their corporate governance practices. This research provides several contributions; introducing moral aspects from governance by behavioural theory is used to understand governance phenomena, application of non positivist methodological aspects in accounting research, so that issues are answered through the social constructionist ontology and contribute to literature by providing a model of the ethics process for enhancing governance practices. Overall, this research offer a new perspective on the corporate governance concept, as it represents a pluralism in governance approach. Due to several limitation faced in undertaking this research, it is suggested that future research examines in - depth case studies. Additional empirical work such as investigating relationship between the variables is also recommended.